Improving practice around use of linked protected characteristics data in Scotland - Robson, Siân; Oldfield, Katie (International Journal of Population Data Science, 2026)
This project brings together information from research, practice and public views to make recommendations about safeguarding and use of protected characteristic data from administrative sources. The work was prompted by considering safeguarding of the Equalities Protected Characteristics Dataset (a collation of protected characteristics data for the Scottish population), but applies to other data sources. Information on the benefits, risks and current practice around use of protected characteristics data for research was gathered through desk-based research and discussions with subject matter experts. A survey and roundtable were conducted with data owners, data providers and researchers to discuss current practice and possible improvements within the system regarding use of protected characteristic data. This work identified possibilities for greater alignment in the data access approvals process and for support for researchers and access panel members. Engagement will be conducted with relevant communities and experts on specific protected characteristics to seek views on collection and use of data and to involve them in development of the following outputs. Resources on good practice in use of protected characteristics data from administrative sources Recommendations for how Research Data Scotland’s approval panel should consider applications to use protected characteristics data available within the Researcher Access Service Suggestions of safeguarding processes which could be applied across other data providers in Scotland This work will complement and contribute to related engagement work taking place across the UK and inform policy and practice around use of protected characteristics data for research.